2018
DOI: 10.1111/jch.13463
|View full text |Cite
|
Sign up to set email alerts
|

Winter morning surge in blood pressure after the Great East Japan Earthquake

Abstract: The great earthquake triggered a powerful tsunami, which provoked catastrophic damage, especially in coastal regions. Almost all buildings were completely destroyed, and thousands of residents in the affected areas were forced to move from their own homes or apartments to temporary housing. Even today, more than 7 years after the disaster, many of the displaced victims continued to live in temporary housing. The quality of life in such housing may affect the health of evacuees, since temporary housing tends to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Another factor that needs to be considered is the housing conditions, which are especially important for elderly hypertensive patients. A study by Nishizawa et al analyzed the winter morning surge according to the housing conditions after the Great East Japanese earthquake and found that hypertensive patients aged ≥75 years who lived in self‐owned older homes showed a significantly higher risk for being in the highest quintile (≥20 mm Hg) of the morning BP surge (odds ratio 5.21; 95% confidence interval, 1.49‐18.22; P = .010) compared to that for individuals who lived in better insulated temporary housing provided by the government . The results from this study show the importance of adequate indoor insulation and heating to minimize the winter morning BP surge, especially in elderly individuals.…”
Section: Information and Communication Technology (Ict)–based Home Bpmentioning
confidence: 61%
“…Another factor that needs to be considered is the housing conditions, which are especially important for elderly hypertensive patients. A study by Nishizawa et al analyzed the winter morning surge according to the housing conditions after the Great East Japanese earthquake and found that hypertensive patients aged ≥75 years who lived in self‐owned older homes showed a significantly higher risk for being in the highest quintile (≥20 mm Hg) of the morning BP surge (odds ratio 5.21; 95% confidence interval, 1.49‐18.22; P = .010) compared to that for individuals who lived in better insulated temporary housing provided by the government . The results from this study show the importance of adequate indoor insulation and heating to minimize the winter morning BP surge, especially in elderly individuals.…”
Section: Information and Communication Technology (Ict)–based Home Bpmentioning
confidence: 61%
“…The times and places at which the surge BP is generated would be the most risky times/places for an individual's cardiovascular event onset. Even among well‐controlled hypertensive patients, the morning BP surge remains significant in the winter . Anticipation medicine for cardiovascular diseases—which both anticipates pathological surge BP based on the previous time series of individual BP data and avoids the generation of surge BP—is an ideal future practical direction to take in order to decrease the gap between the guidelines and individualized medicine in the era of ICT‐based “real‐world” big data analysis and feedback systems.…”
Section: Blood Pressure Surge‐based Anticipation Medicinementioning
confidence: 99%
“…There is also significant seasonal variation in BP. Both BP and BPV are increased in the winter, and inverse and exaggerated seasonal BP variation increased the risk of CVD . Pathological thresholds are ≥180 mm Hg for maximum SBP, ≥20 mm Hg for SD of visit‐to‐visit systolic BPV, ≥20 mm Hg for orthostatic SBP change (increase or decrease by ≥20 mm Hg), and <0 mm Hg or ≥20 mm Hg for winter increase in SBP (SBP in winter minus SBP in summer; seasonal variation).…”
Section: Bp Scorementioning
confidence: 99%